Activation of the cholinergic anti-inflammatory pathway ameliorates postoperative ileus in mice. - The, F; Boeckxstaens, G; Snoek, SA; Cash, J; Bennink, R; Larosa, G; van den Wijngaard, R; Greaves, D; de Jonge, W (2007)
BACKGROUND and AIMS: We previously showed that intestinal inflammation is reduced by electrical stimulation of the efferent vagus nerve, which prevents postoperative ileus in mice. We propose that this cholinergic anti-inflammatory pathway is mediated via alpha7 nicotinic acetylcholine receptors expressed on macrophages. The aim of this study was to evaluate pharmacologic activation of the cholinergic anti-inflammatory pathway in a mouse model for postoperative ileus using the alpha7 nicotinic acetylcholine receptor-agonist AR-R17779. METHODS: Mice were pretreated with vehicle, nicotine, or AR-R17779 20 minutes before a laparotomy (L) or intestinal manipulation (IM). Twenty-four hours thereafter gastric emptying was determined using scintigraphy and intestinal muscle inflammation was quantified. Nuclear factor-kappaB transcriptional activity and cytokine production was assayed in peritoneal macrophages. RESULTS: Twenty-four hours after surgery IM led to a delayed gastric emptying compared with L (gastric retention: L(saline) 14% +/- 4% vs IM(saline) 38% +/- 10%, P = .04). Pretreatment with AR-R17779 prevented delayed gastric emptying (IM(AR-R17779) 15% +/- 4%, P = .03). IM elicited inflammatory cell recruitment (L(saline) 50 +/- 8 vs IM(saline) 434 +/- 71 cells/mm(2), P = .001) which was reduced by AR-R17779 pretreatment (IM(AR-R17779) 231 +/- 32 cells/mm(2), P = .04). An equimolar dose of nicotine was not tolerated. Subdiaphragmal vagotomy did not affect the anti-inflammatory properties of AR-R17779. In peritoneal macrophages, both nicotinic agonists reduced nuclear factor kappaB transcriptional activity and proinflammatory cytokine production, with nicotine being more effective than AR-R17779. CONCLUSIONS: AR-R17779 treatment potently prevents postoperative ileus, whereas toxicity limits nicotine administration to ineffective doses. Our data further imply that nicotinic inhibition of macrophage activation may involve other receptors in addition to alpha7 nicotinic acetylcholine receptor.